Lipid deposition on contact lenses in symptomatic and asymptomatic contact lens wearers. Issue 1 (February 2021) - Omali, Negar Babaei; Subbaraman, Lakshman. N.; Heynen, Miriam; Lada, Mark; Canavan, Kristy; Fadli, Zohra; Ngo, William; Jones, Lyndon
Highlights: Symptomatic and asymptomatic contact lens wearers were enrolled in the study and were fit into senofilcon A lenses. Lipid amounts were quantified from worn senofilcon A lenses after 14 days of wear. The asymptomatic group showed a greater amount of lipid deposition, suggesting the possibility that lipid deposition may be associated with more comfortable lens wear. Abstract: Purpose: Lipid deposition on contact lenses (CL) has traditionally been believed to reduce comfort during CL wear. The purpose of this study was to quantify lipid deposition on CL in a group of symptomatic and asymptomatic adapted CL wearers. Methods: This was a single-masked, randomized clinical trial. Only confirmed symptomatic (comfortable lens wear time (CWT) < 8 h and a noticeable reduction in comfort over the course of the day) and asymptomatic (CWT > 10 h and minimal reduction in comfort over the course of the day) participants were recruited to participate in the study. Participants wore senofilcon A lenses in combination with a polyquaternium-based care solution (OPTI-FREE Replenish). Worn CL samples were collected on Day 14. Deposited lipid amounts from the lenses (including cholesteryl ester, cholesterol and triolein) were quantified using a liquid chromatography-mass spectrometry technique. Results: Lipid deposition was significantly higher in CL extracts of asymptomatic wearers compared to the symptomatic wearers for all lipid types quantified, including cholesteryl ester (2.1 ± 0.6 vs 1.6 ± 0.5 log μg/lens), cholesterol (1.5 ± 0.3 vs 1.1 ± 0.3 log μg/lens) and triolein (0.3 ± 0.2 vs 0.1 ± 0.1 log μg/lens) (all p < 0.002). The amount of cholesteryl ester deposited was greatest ( p = 0.0001), followed by cholesterol, then triolein, for both the asymptomatic and symptomatic groups (both p = 0.0001). Conclusion: This study demonstrated that the asymptomatic group deposited a significantly greater amount of lipid on their CL. Although lipid levels measured are considered low to trigger any observable clinical deposition, they may influence other clinical outcomes, particularly comfort.